2005
DOI: 10.1159/000084513
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fibroids on Fertility in Patients Undergoing Assisted Reproduction

Abstract: Objective: The aim of this study is to evaluate the current data to understand the impact of intramural leiomyomata on pregnancy outcome in assisted reproduction. Patients and Methods: In this review, articles were found by means of computerized Medline and Cochrane Library search using the key words uterine myomata, leiomyomata, fibroids, implantation, pregnancy, infertility and in vitro fertilization. Limitations were English, human, 1990–2002. Inclusion criteria were pregnancy data on in vitro fertilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 16 publications
0
65
0
3
Order By: Relevance
“…Korlátozott számban elérhetők ilyen jellegű munkák, amelyek eredményei alapján a submucosus myomák eltávolításának fertilitásjavító hatása lehet, míg az intramuralis gócok eltávolításának szükségessége még kérdé-ses [14]. A méh üregét deformáló gócok méhtükrözés során történő eltávolítása Bettocchi munkája alapján is indokoltnak tűnik [16], míg Benecke vizsgálatai alapján az intramuralis myomák eltávolítása egyértelműen javítja az asszisztált reprodukciós technikák eredményességét [17].…”
Section: öSszefoglaló Közleményunclassified
“…Korlátozott számban elérhetők ilyen jellegű munkák, amelyek eredményei alapján a submucosus myomák eltávolításának fertilitásjavító hatása lehet, míg az intramuralis gócok eltávolításának szükségessége még kérdé-ses [14]. A méh üregét deformáló gócok méhtükrözés során történő eltávolítása Bettocchi munkája alapján is indokoltnak tűnik [16], míg Benecke vizsgálatai alapján az intramuralis myomák eltávolítása egyértelműen javítja az asszisztált reprodukciós technikák eredményességét [17].…”
Section: öSszefoglaló Közleményunclassified
“…fertility have led to the need for uterine leiomyomas analysis in relation to the gestation [1]. The relationship between the uterine fibroid and infertility, except in evident cases (i.e.…”
Section: 2478/arsm-2014-0025mentioning
confidence: 99%
“…Disorders of microvascularisation in endometrium, and the influences on the gestational implantation stages are still not fully revealed. Uterine leiomyoma is present in approximately 10% of the cases on patients with infertility [1,2]. If it is demonstrated a causal link between the uterine fibroids and infertility, than surgical treatment should be indicated [2].…”
Section: 2478/arsm-2014-0025mentioning
confidence: 99%
“…Fibroids are present in approximately 5-10% of the patients presenting with infertility; however, they were found to be the sole identified factor in only 1-2,4% of the infertile patients [13,14]. Andreoli researched the statistics of many authors and concluded that out of 3712 cases of myomectomies for fibroids associated with infertility, 1311 patients (36,1%) got pregnant [15].…”
Section: Fibroids and Infertilitymentioning
confidence: 99%